The effect of obstacle running training on special physical abilities and 100-meter running achievement - Abood, Hussein (Journal of Physical Education, 2023)
The importance of research has crystallized in building obstacle running training in order to raise the special physical abilities of female runners in order to achieve success. Then we can find a training method that participates in raising the level of effectiveness for the better. The aim of the research is to identify the special physical abilities and to complete the 400 m hurdles for young women, as well as to Preparing hurdle-running exercises for the different stages of running, and identifying the effect of these exercises on specific physical abilities and achievement. The researcher used the experimental method by designing two equal control and experimental groups. The research population was determined intentionally from young female 100-meter runners, as the sample was divided into two groups, a control group and its number (4) Female runners and an experimental group (4). The experimental sample group was chosen by lottery from among (8) female runners. The training with this approach was correct and there was development in that effectiveness at the level of the experimental sample. This does not mean that the training of the control group was incorrect and no noticeable development occurred at the level of the control sample.